Spectrophotometric Methods for the Assay of Tylosin - Devala Rao, Garikapati (Asian Journal of Chemistry, 2016)
Two simple, sensitive and reproducible spectrophotometric methods (Method A and Method B) are developed for the determination of tylosin (TS) in bulk and dosage forms. These methods are based on the formation of coloured species on treatment of tylosin with 3-methyl-2-benzothiazolinone hydrazone hydrochloride (MBTH) and Fe(III) ions [Method A] and oxidation/reduction with Folin-Ciocalteu (FC) reagent under alkaline conditions [Method B].